Labour market perceptions of students at a Technical and Vocational Education and Training (TVET) college in Grahamstown, South Africa - Khambule, Nelisa (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
In the context of South Africa, the supply of intermediate to high-level skills is central to economic growth and development. The post-school education and training sector is a critical source of these skills. Technical and Vocational Education and Training (TVET) colleges are expected to provide the intermediate to high-level skills that are required in a fast-changing global and national economy. In addition to fulfilling the goal of meeting the skills needs of the country, TVET colleges are expected to expand access to education and training opportunities and create pathways that will ensure smooth transitions for learners from college to employment. Using the third-generation labour market segmentation approach to the study of labour markets, this study sought to investigate the various socio-political factors that influence TVET college students' perceptions about employment opportunities in the labour market with a NCV qualification. Using a qualitative methodology, this research investigated whether TVET students at Eastcape Midlands College felt adequately prepared for the labour market with their prospective post-secondary school qualification. The findings varied, with some students being of the view that the theoretical component of their programme of study could be improved to better prepare them for the labour market, and others, being of the view that the practical component could be improved. At a general level, the findings showed that the students did not have perfect knowledge of the availability of employment opportunities for their prospective qualifications.
Keywords: Eastcape Midlands College (Makhanda, -- South Africa) -- Students -- Attitudes; College students -- South Africa -- Makhanda -- Attitudes; College graduates -- Employment -- South Africa; Labor market -- South Africa; Employability -- South Africa